Different training intensities induced autophagy and histopathology appearances potentially associated with lipid metabolism in wistar rat liver. Issue 5 (May 2020) - Gunadi, Julia Windi; Tarawan, Vita Murniati; Daniel Ray, Hamidie Ronald; Wahyudianingsih, Roro; Lucretia, Teresa; Tanuwijaya, Fenny; Lesmana, Ronny; Supratman, Unang; Setiawan, Iwan
Abstract: Introduction: Aerobic training has a beneficial effect on enhancing liver functions. Autophagy might potentially play a role in preventing excessive lipid accumulation, regulating oxidative stress, and inflammation in the liver. Objective: To investigate the potential linking role of autophagy-related gene expressions and protein levels with histopathology changes in Wistar rat livers after treadmill training under different intensities. Methods: 20 rats were divided into 4 groups (control, low intensity, moderate intensity, and high intensity). 8 weeks of treadmill training was conducted with a frequency of 5 days per week, for a duration of 30 min per day. Liver histopathology was studied using hematoxylin-eosin, and oil red O staining. RNA and protein from the liver tissues were extracted to examine the autophagy-related gene (LC3, p62) and protein levels (Beclin, ATG5, LC3, p62). The gene expressions of CPT1a, CD36, FATP 2, 3, 5, GLUT2, and FGF21 were also studied. Results: Different intensities of training might potentially modulate autophagy-related gene expressions in rat livers. LC3 and p62 mRNA expressions in moderate and high intensities decreased compared to control. Beclin, ATG5, and LC3 protein level increased compared to control, while p62 protein level decreased compared to control. Whereas for the other genes, we found an increase in CPT1a, but we did not observed any changes in the expression of the other genes. Interestingly, autophagy-related gene expressions might be correlated with the changes of sinusoidal dilatation, cloudy swelling, inflammation, and lipid droplets of the liver tissues. Conclusion: Moderate and high intensities of training induce autophagy activity, combined with a shift in metabolic zonation in liver that might be potentially correlated with lipophagy. Our results showed the potential interplay role between autophagy and liver histopathology appearances as a part of the adaptation process to training. Abstract : Biological sciences; Exercise; Animal physiology; Health sciences; Physiology; Treadmill training; Lipid droplets; Autophagy; Lipophagy; Histopathology